Outcomes of Mild Aortic Regurgitation After Transcatheter Aortic Valve Replacement. Issue 2 (4th March 2021) - Chahine, Johnny; Kadri, Amer N.; Gajulapalli, Rama Dilip; Lak, Hassan; Krishnaswamy, Amar; Reed, Grant; Perez, Oscar; Puri, Rishi; Popovic, Zoran; Verma, Beni Rai; Kaur, Manpreet; Gad, Mohamed M.; et al.
ABSTRACT: Background : There has been an explosion in the clinical application of transcatheter aortic valve replacement (TAVR) worldwide. While moderate and severe grades of paravalvular regurgitation (PVR) are established as poor prognostic indicators, the impact of mild PVR is unclear. We therefore aimed to compare outcomes after TAVR between those who develop mild PVR versus none or trivial PVR. Methods : We identified 1, 098 consecutive patients who underwent TAVR from January 2014 to December 2017. The primary outcome was all-cause mortality using Kaplan Meier curves. The secondary outcomes included heart failure readmissions and the composite endpoints of early safety and clinical efficacy according to VARC-2 definitions. Results : The median age was 82 years, 43% were females, and 94% were Caucasian. The procedure was done through a transfemoral approach, the indication for TAVR was severe AS in 97% of cases, and 72% had an Edwards SAPIEN 3 Transcatheter Heart Valve implanted. Mild PVR was seen in 191 (17.4%) patients, and the rest (82.6%) had no or trivial post-TAVR PVR. Mortality at 30-days and 1 year was similar between none/trivial and mild PVR groups (1.6% vs 1.7%, p = 0.93 & 6.3% vs 8.8%, p = 0.31). HF-related hospitalizations were the same at 30 days as well as 1 year in both groups (1.9% vs 0.8%, p = 0.209 and 4.5% vs 6.3%, p = 0.461). Conclusion : Although mild PVR is seen in approximately one-fifth of patients after TAVR, patients with mild PVR have similar outcomes compared to those with none or trivial PVR. Abbreviations: AR: Aortic Regurgitation; AV: Aortic Valve; HF: Heart Failure; VARC: Valve Academic Research Consortium; LVOT: Left Ventricular Outflow Tract; LVEF: Left Ventricular Ejection Fraction; PVR: Paravalvular Aortic Regurgitation; TAVR: Transcatheter Aortic Valve Replacement; TF: Transfemoral